Mechanical and shrinkage performance of 3D-printed rubberised engineered cementitious composites. (11th July 2022) - Aslani, Farhad; Dale, Ryan; Hamidi, Fatemeh; Valizadeh, Afsaneh
Highlights: Rubberised engineered cementitious composites have been developed for 3DP. Compressive, flexural and shrinkage behaviour of developed composites have been investigated. Printed specimens in the fibre-parallel direction showed 37% less drying shrinkage. Samples loaded in perpendicular direction led to 4% higher 28-day compressive strength. Samples loaded in perpendicular direction led to 47% higher 28-day flexural strength. Abstract: Taking the advantages of 3D concrete printing (3DCP) and tackling the environmental issues related to the waste tires, current paper evaluates the material behaviour of rubberised engineered cementitious composites (ECC) using waste crumb rubber (CR) aggregates and polyvinyl alcohol (PVA) fibres, manufactured through 3DCP. To elaborate on the role of PVA fibres on the material properties, two different control mix designs were prepared through conventional mould-casting method, including control mix design without PVA fibres and ECC with PVA fibres equal to 1.75 vol% of binder. Thereafter, using the control ECC mix design, four mix designs containing 5, 10, 15, and 20% CR aggregates as replacement of fly ash, were prepared to assess the effect of CR on the mechanical performance of ECC. The prepared mix designs were subjected to compressive and flexural strengths, and shrinkage tests, and the rubberised ECC containing 5% CR was selected for 3DCP as it revealed superior compressive, flexural and shrinkage behaviour. Results obtained for 3D-printed specimens confirmed the dominant role of anisotropy on the material performance, which was very pronounced for flexural behaviour of printed elements. Comparing to the samples loaded in perpendicular direction, loading in the parallel direction to the fibre orientation (X direction) led to 3 and 4% higher 7- and 28-day compressive strengths, and loading parallel to the fibre alignment along the longitudinal axis of the specimen (Z direction) resulted in 104% and 47% increase in the 7- and 28-day flexural strengths, respectively. Moreover, printed specimens in the fibre-parallel direction showed 37% less drying shrinkage comparing to those printed in the perpendicular direction. Additionally, 3D-printed elements represent superior performance in terms of compressive strength, ductile characteristics, flexural behaviour, and shrinkage performance over the mould-casted ones.